Protein kinase in HeLA nucleosomes: a reevaluation of the interactions of histomes with the ends of core particle DNA. - Simpson, R T (1978)
HeLa chromatin core particles contain a protein kinase which transfers phosphate from ATP to both nonhistone proteins and histones. The enzyme preferentially modifies H3 among the histones; about 7% of the H3 molecules in the nucleoprotein are modified at saturation. Activity of this kinase likely contributed to earlier results using crosslinking methodology to study which histones interact with the ends of core particle DNA. When the kinase is largely removed by sedimentation of core particles through sucrose gradients containing 0.45 M NaCl, crosslinking of the 5'-terminal label on DNA is observed only to histone H3. The overall efficiency of the crosslinking reaction is about 15%. The origin of the 5'-terminal 32P previously assigned as crosslinked to H4 is not explained by the current experiments.